2010
DOI: 10.1093/europace/euq439
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of angiotensin II-receptor blocker vs. dihydropiridine calcium channel blocker in the treatment of paroxysmal atrial fibrillation with hypertension (J-RHYTHM II Study)

Abstract: In patients with paroxysmal AF and hypertension, treatment of hypertension by candesartan did not have an advantage over amlodipine in the reduction in the frequency of paroxysmal AF (umin CTR C000000427).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 32 publications
1
76
2
5
Order By: Relevance
“…Leczenie statyną nie zapobiega również AF w innych sytuacjach klinicznych [692,693]. Nie udało się także udowodnić przekonujących korzyści ze stosowania wielonienasyconych kwasów tłusz-czowych [241,[694][695][696][697][698]. Roli antagonistów aldosteronu w leczeniu AF nie oceniano dokładnie u ludzi.…”
Section: Antyarytmiczne Działanie Leków Nieantyarytmicznychunclassified
“…Leczenie statyną nie zapobiega również AF w innych sytuacjach klinicznych [692,693]. Nie udało się także udowodnić przekonujących korzyści ze stosowania wielonienasyconych kwasów tłusz-czowych [241,[694][695][696][697][698]. Roli antagonistów aldosteronu w leczeniu AF nie oceniano dokładnie u ludzi.…”
Section: Antyarytmiczne Działanie Leków Nieantyarytmicznychunclassified
“…In two retrospective analyses, ACEls and ARBs in addition to antiarrhythmic agents neither prevent progression to permanent AF 60 or AF recurrence. 61 Recently, the Japanese Rhythm Management Trial for Atrial Fibrillation (J-RHYTHM) II study 62 also demonstrated no reduction in the AF recurrence with candesartan as compared with amlodipine as monitored by daily transtelephonic ECG recording in 318 hypertensive patients with paroxysmal AF. Furthermore, the preliminary data of the prospective, randomized study------Angiotensin II Antagonist in Paroxysmal Atrial Fibrillation (ANTIPAF)------ 30,63 showed that olmesartan did not prevent AF in the absence of anitarrhythmic agents as compared with placebo.…”
Section: Raas Activationmentioning
confidence: 99%
“…Valsartan also did not reduce the recurrent AF rate in the Gruppo Italiano per lo Studio della Sopravvivenza nell'Infarto Miocardico-Atrial Fibrillation (GISSI-AF) trial. 11 The J-RHYTHM II Study 12 in Japan also demonstrated that candesartan did not have a significant advantage over amlodipine in reducing recurrent AF. Patton and colleagues 13 reported that N-terminal probrain natriuretic peptide (NT-ProBNP) serves as a biomarker for AF recurrence regardless of the patients' race/ethnicity.…”
mentioning
confidence: 99%